Chinese military medical teams in the Ebola outbreak of Sierra Leone. Issue 3 (7th January 2016) - Lu, Yinying; Rong, G; Yu, S P; Sun, Z; Duan, X; Dong, Z; Xia, H; Zhan, N; Jin, C; Ji, J; Duan, H
Abstract : The 2014–2015 Ebola virus disease (EVD) epidemic in West Africa was the largest in history. The three most affected countries, Guinea, Liberia and Sierra Leone, have faced enormous challenges in controlling transmission and providing clinical care for patients with EVD. The Chinese government, in response to the requests of the WHO and the governments of the affected countries, responded rapidly by deploying Chinese military medical teams (CMMTs) to the areas struck by the deadly epidemic. A total of three CMMTs, comprising 115 military medical professionals, were rotationally deployed to Freetown, Sierra Leone to assist with infection prevention and control, clinical care and health promotion and training. Between 1 October 2014 and 22 March 2015, the CMMTs in Sierra Leone admitted and treated a total of 773 suspected and 285 confirmed EVD cases. Among the 285 confirmed cases, 146 (51.2%) patients survived after treatment. In addition, the CMMTs maintained the record of zero infections among healthcare workers and zero cross-infections between quarantined patients. In this manuscript, we aim to give an overview of the mission, and share our best practices experience on predeployment preparedness, EVD holding and treatment centre building and EVD case management.